Varietal Differences in Plant Growth, Phosphorus Uptake and Yield Formation in Two Maize Inbred Lines Grown Under Field Conditions - Fan-jun CHEN; Xiang-sheng LIU; Guo-hua MI (Journal of Integrative Agriculture, 2012)
Selection for phosphorus (P)-efficient genotypes and investigation of physiological mechanisms for P-use efficiency in maize has mainly been conducted at the seedling stage under controlled greenhouse conditions. Few studies have analyzed characteristics of plant growth and yield formation in response to low-P stress over the whole growth period under field conditions. In the present study, two maize inbred lines with contrasting yield performances under low-P stress in the field were used to compare plant growth, P uptake and translocation, and yield formation. Phosphorus accumulation in the P-efficient line 154 was similar to that of line 153 under high-P. Under low-P, however, P uptake in line 154 was three times greater than that in line 153. Correspondingly, P-efficient line 154 had a significantly higher yield than P-inefficient line 153 under low-P conditions (Olsen-P=1.60 mg kg−1), but not under high-P conditions (Olsen-P= 14.98 mg kg−1). The yield difference was mainly due to differences in the number of ears per m2, that is, P-efficient line 154 formed many more ears under low-P conditions than P-inefficient line 153. Ear abortion rate was 53% in the P-inefficient line 153, while in line 154, it was only 30%. Low-P stress reduced leaf appearance, and delayed anthesis and the silking stage, but increased the anthesis-silking interval (ASI) to a similar extent in both lines. The maximum leaf area per plant at silking stage was higher in P-efficient line 154 than in P-inefficient line 153 under both P conditions. It is concluded that low-P stress causes intense intraspecific competition for limited P resources in the field condition which gives rise to plant-to-plant non-uniformity, resulting in a higher proportion of barren plants. As soon as an ear was formed in the plant, P in the plant is efficiently reutilized for kernel development.